2009
DOI: 10.1093/cvr/cvp233
|View full text |Cite
|
Sign up to set email alerts
|

Reducing ischaemia/reperfusion injury through  -opioid-regulated intrinsic cardiac adrenergic cells: adrenopeptidergic co-signalling

Abstract: ICA cells constitute a delta-opioid-regulated adrenopeptidergic paracrine system conferring robust cardioprotection through beta(2)-AR/CGRP-R co-signalling, resulting in the activation of an anti-apoptotic pathway during ischaemia/reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…Yao et al (33) reported that activation of the δ-opioid receptor reduces the apoptosis of myocardial cells through inhibition of the ERK and IP3 pathways. Furthermore, Huang et al (34) reported that activation of the δ-opioid receptor inhibits apoptosis by promoting CGRP expression in myocardial cells. A cell-type specific discrepancy between liver cells and myocardial cells may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (33) reported that activation of the δ-opioid receptor reduces the apoptosis of myocardial cells through inhibition of the ERK and IP3 pathways. Furthermore, Huang et al (34) reported that activation of the δ-opioid receptor inhibits apoptosis by promoting CGRP expression in myocardial cells. A cell-type specific discrepancy between liver cells and myocardial cells may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al demonstrated that DPDPE markedly increased phosphorylated Akt levels in mouse cardiomyocytes. 40 In this study, we did not analyze the effect of PKC inhibition on Akt content as a result of DOR activation and thus the involvement of Akt signaling after DOR activation in MSCs remains unclear.…”
Section: Signaling Pathway For Msc Survival By Dor Activationmentioning
confidence: 96%
“…Among several potential mechanisms, Akt activation has been implicated as one of the key signaling pathways underling postconditioning mediated heart protection [1, 2], although species difference has been reported [3]. The mammalian heart possesses adrenopeptidergic neuroparacrine system consisting of intrinsic cardiac adrenergic (ICA) cells [46]. ICA cells synthesize and release epinephrine and calcitonin gene-related peptide (CGRP), stimulating myocardial β 2 -adrenoreceptor (β 2 -AR) and CGRP-receptors [5, 6], both of which being coupled to the adenylate cyclase-cAMP-dependent signaling pathway [79].…”
Section: Introductionmentioning
confidence: 99%